A ‘look’ into conjunctivitis - F. Kathrada (South African Family Practice)
Conjunctivitis is a common condition characterised by inflammation of the conjunctiva and is the most likely diagnosis in a patient with a red eye and discharge. Acute conjunctivitis is usually a self-limiting condition or one that is easily treated with topical ophthalmic preparations in most cases. Viral conjunctivitis is the most common cause of conjunctivitis followed by bacterial conjunctivitis. Purulent discharge and adherence of the eyelids upon awakening are strong indicators of bacterial conjunctivitis, however other similarities in presentation of conjunctivitis often leads to misdiagnoses. Acute viral conjunctivitis is most commonly caused by adenoviruses and allergic conjunctivitis is usually caused by seasonal pollens. Acute viral conjunctivitis is treated symptomatically while the use of topical antibiotics are useful in limiting the duration of conjunctivitis with a bacterial aetiology. Allergic conjunctivitis is also treated symptomatically with topical antihistamine/mast cell stabiliser preparations. Conjunctivitis secondary to sexually transmitted diseases such as chlamydia or gonorrhoea require systemic antimicrobials in addition to topical treatment.